Influence of additions of synthetic anhydrous calcium carbonate polymorphs on nanolime carbonation. (20th December 2019) - Ševčík, Radek; Mácová, Petra; Estébanez, Marta Pérez; Viani, Alberto
Highlights: Influence of synthetic anhydrous CaCO3 on nanolime carbonation was investigated. Carbonation was accelerated, with a control exerted by specific surface of solids. Use of synthetic CaCO3 resulted an effective seeding method for polymorph control. Addition of aragonite reduced desiccation cracks in the obtained carbonated product. Abstract: The influence of synthetic anhydrous calcium carbonate polymorphs, calcite, vaterite and aragonite, on carbonation of nanolime suspension, has been investigated. The higher rates of carbonation observed after 7 days in mixtures containing vaterite and aragonite particles, found explanation in the control exerted by heterogeneous nucleation on the water-mediated reaction mechanism and in the enhanced carbon dioxide diffusivity in the sample volume, both facilitated by the higher specific surface of the powders and the microporous sample fabric. Introduction of synthetic calcium carbonate allowed for exerting control on formed polymorphs, subverting the order of their (meta-)stability. The peculiar microstructure obtained by adding aragonite rod-like particles, mitigates the propagation of desiccation cracks (which impair continuity of the carbonated nanolime film). The mechanism, although still not completely understood, likely involves the regulation of evaporation of liquid fraction and redistribution of the tensional stresses during drying and nanolime crystallization. The obtained results provide new insights into the crystallization of carbonates from nanolime particles and may help in the design of innovative compatible products for consolidation of lime-based materials and carbon dioxide sequestration.